In Vitro Antitumor Effects of AHR Ligands Aminoflavone (AFP 464) and Benzothiazole (5F 203) in Human Renal Carcinoma Cells - Luzzani, Gabriela Andrea (2017)
We investigated activity and mechanism of action of two AhR ligand antitumor agents, AFP 464 and 5F 203 on human renal cancer cells, specifically examining their effects on cell cycle progression, apoptosis, and migration. TK-10, SN12C, Caki-1, and ACHN human renal cancer cell lines were treated with AFP 464 and 5F 203. We evaluated cytotoxicity by MTS assays, cell cycle arrest, and apoptosis by flow cytometry and corroborated a mechanism of action involving AhR signal transduction activation. Changes in migration properties by wound healing assays were investigated: 5F 203-sensitive cells show decreased migration after treatment, therefore, we measured c-Met phosphorylation by Western blot in these cells. A 5F 203 induced a decrease in cell viability which was more marked than AFP 464. This cytotoxicity was reduced after treatment with the AhR inhibitor α-NF for both compounds indicating AhR signaling activation plays a role in the mechanism of action. A 5F 203 is sequestered by TK-10 cells and induces CYP1A1 expression; 5F 203 potently inhibited migration of TK-10, Caki-1, and SN12C cells, and inhibited c-Met receptor phosphorylation in TK-10 cells. AhR ligand antitumor agents AFP 464 and 5F 203 represent potential new candidates for the treatment of renal cancer. A 5F 203 only inhibited migration of sensitive cells and c-Met receptor phosphorylation in TK-10 cells. c-Met receptor signal transduction is important in migration and metastasis. Therefore, we consider that 5F 203 offers potential for the treatment of metastatic renal carcinoma. J. Cell. Biochem. 118: 4526–4535, 2017. © 2017 Wiley Periodicals, Inc.